Karakter Morfologis dan Molekular Macrobrachium spp. dari Sungai Opak Daerah Istimewa Yogyakarta - Trijoko T; Niken Satuti Nur Handayani; Anita Widianawati; Rury Eprilurahman (Biogenesis: Jurnal Ilmiah Biologi, 2015)
Several rivers flow across Daerah Istimewa Yogyakarta (DIY includes Opak River which it’s upstream located on Merapi Volcano area. The river has a lot of biological resources, includes prawns. Freshwater prawns (Macrobrachium spp.) has important role in maintaining the balance of freshwater ecosystems. The purpose of this research was to determine species diversity of Macrobrachium spp. and to understand the morphological and molecular characters of them. Phenetic similarity was analyzed using 74 morphological characters, ISSR1 and ISSR3 primers. The results were analyzed using a program MVSP 3.1 (Multi- Variate Statistical Package) to obtain a dendogram that showed both intra-and interspecies similarity of Macrobrachium spp. Six species of Genus Macrobrachium were identified, they are Macrobrachium pilimanus, M. sintangense, M. lanchesteri, M. cowlesi, M. latidactylus, and M. equidens. Both morphological and molecular analyses show two major clusters with the similarity of 55.6% for morphology and 21.52% for molecular. Based on morphological and molecular characters analysis, we concluded that phenetic similarity of Macrobrachium spp. in Opak River was affected by the morphological structure of the second pereiopod, habitat type, size and number of eggs, as well as the type of larval development.Keywords: characters, Macrobrachium, molecular, morphology, Opak River